2022
DOI: 10.1161/jaha.122.026254
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Hepatic Native T1 and Extracellular Volume Fraction in Patients with Pulmonary Arterial Hypertension

Abstract: Background Right heart failure may lead to impaired liver perfusion and venous congestion, resulting in different extents of liver fibrosis. However, whether hepatic tissue deterioration determined by native T1 mapping and extracellular volume fraction using cardiac magnetic resonance imaging is associated with poor outcomes in patients with pulmonary arterial hypertension remains unclear. Methods and Results A total of 131 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Hepatic native T1 and extracellular volume fraction of the liver in PAH were associated with an increased risk of death. 25 The hepatic native T1 value was not associated with transaminases providing validation of our congestive hepatopathy group (which was not defined by transaminase levels). Other techniques of ultrasound elastography (providing a liver fibrosis index) showed an association with clinical worsening in a very small number of PAH patients.…”
Section: Discussionmentioning
confidence: 66%
“…Hepatic native T1 and extracellular volume fraction of the liver in PAH were associated with an increased risk of death. 25 The hepatic native T1 value was not associated with transaminases providing validation of our congestive hepatopathy group (which was not defined by transaminase levels). Other techniques of ultrasound elastography (providing a liver fibrosis index) showed an association with clinical worsening in a very small number of PAH patients.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to purely cardiac fields of application, non-cardiac tissues are also increasingly being examined by parametric imaging. For example, a very recent study by Guo et al investigated the value of hepatic T1 mapping in patients with PH and demonstrated, that hepatic T1 values were predictive for adverse cardiovascular events [ 10 ]. Furthermore, Tilman et al investigated right ventricular and left ventricular T2 blood pool values in patients with left-to-right shunting and showed that the “right-to-left-ventricular blood pool T2 ratio—RVT2/LVT2” might be a novel imaging biomarker for detection of shunts without the need for additive phase-contrast acquisitions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%